The Linear Theory of Economic Development - Loubaki, Diana (IJRDO - Journal of Applied Management Science, 2017)
This article is a theory of economic development which shows that under development andcivil wars in Africa comes mostly from ethnic divisions. Therefore, since developmenteconomics dynamics is linear, development take-off is reached at the locus on the space-timewhere all the ethnics take place inside the production sector without distinction of theirorigins. Thus, the article promotes incentives to invest in human capital accumulation andlabour force participation in the society as a mechanics of economic development since it mayfight ethnic division in least advanced economies.